2017
DOI: 10.1002/hbm.23911
|View full text |Cite
|
Sign up to set email alerts
|

Automated quality assessment of structural magnetic resonance images in children: Comparison with visual inspection and surface‐based reconstruction

Abstract: Motion-related artifacts are one of the major challenges associated with pediatric neuroimaging. Recent studies have shown a relationship between visual quality ratings of T images and cortical reconstruction measures. Automated algorithms offer more precision in quantifying movement-related artifacts compared to visual inspection. Thus, the goal of this study was to test three different automated quality assessment algorithms for structural MRI scans. The three algorithms included a Fourier-, integral-, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 58 publications
(76 citation statements)
references
References 41 publications
1
75
0
Order By: Relevance
“…In addition to the need for objective exclusion criteria, the current neuroimaging data deluge makes the manual QC of every magnetic resonance imaging (MRI) scan impractical. For these reasons, there has been great interest in automated QC [5][6][7][8] , which is progressively gaining attention [9][10][11][12][13][14][15][16] with the convergence of machine learning solutions. Early approaches [5][6][7][8] to objectively estimate image quality have employed "image quality metrics" (IQMs) that quantify variably interpretable aspects of image quality [8][9][10][11][12][13] (e.g., summary statistics of image intensities, signal-to-noise ratio, coefficient of joint variation, Euler angle, etc.).…”
Section: Background and Summarymentioning
confidence: 99%
“…In addition to the need for objective exclusion criteria, the current neuroimaging data deluge makes the manual QC of every magnetic resonance imaging (MRI) scan impractical. For these reasons, there has been great interest in automated QC [5][6][7][8] , which is progressively gaining attention [9][10][11][12][13][14][15][16] with the convergence of machine learning solutions. Early approaches [5][6][7][8] to objectively estimate image quality have employed "image quality metrics" (IQMs) that quantify variably interpretable aspects of image quality [8][9][10][11][12][13] (e.g., summary statistics of image intensities, signal-to-noise ratio, coefficient of joint variation, Euler angle, etc.).…”
Section: Background and Summarymentioning
confidence: 99%
“…showing that younger participants and male participants are more likely to have lower scan quality (Ducharme et al, 2016;Pardoe et al, 2016;White et al, 2018). These findings once again underline the importance of taking scan quality into account in developmental studies, as scan quality might confound findings attributed to age effects.…”
Section: Exploratory Analyses Of Age and Sex Effects Confirmed Previomentioning
confidence: 56%
“…A recent study found that image quality metrics (e.g., such as background voxels located outside the brain) derived from raw T1-weighted scans indeed affect FreeSurfer derived cortical thickness and surface area (White et al, 2018). However, raw image quality metrics typically use information from noise outside the head (Esteban et al, 2017;Pizarro et al, 2016;White et al, 2018). By using FreeSurfer derived measures from inside the brain we increase the likelihood of detecting artifacts that might remain unnoticed when they do not alter characteristics of the air around the head (Pizarro et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations